The Role of New Media in Building Virtual Community Type Unite - Setiawan, Kurnia; Widitiarsa, Arsa; Razali, Geofakta; Putranto, Algooth (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
New media which is currently developing in line with developments in information technology brings a new dimension to the field of communication. Physical public space is shifting and find a new platform, namely digital public space which brings today's society to live in a connected world. One of the virtual communities on a global scale whose founder came from Indonesia is